2022
DOI: 10.1093/jnci/djac226
|View full text |Cite
|
Sign up to set email alerts
|

Association of longer telomere length in cancer cells and cancer-associated fibroblasts with worse prognosis

Abstract: Background Telomere dysfunction has been reported to be directly involved in carcinogenesis owing to chromosomal instability and immortalization; however, the clinicopathological significance of telomeres remains controversial. We have shown that telomere shortening occurs in normal-appeared duct cells at the initiation and then progresses during the progression of pancreatic cancer. In this study, we determined the clinicopathological and prognostic value of telomere length (TL) in cancer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Furthermore, the telomere length is heritable to a significant extent (Samavat et al, 2021;Vaiserman and Krasnienkov, 2021). Contrary to the above-mentioned studies in which TL was measured in peripheral blood, a more recent study in which TL was measured in cancer cells and cancer-associated fibroblasts (CAFs) found longer telomeres to be associated with worse prognosis in adenocarcinoma and squamous cell carcinoma and acknowledged it as a novel biomarker for the diagnosis of aggressive cancers with poor prognoses (Matsuda et al, 2023). In studies exploring the role of cancer cell telomere length in cancer risk, both shorter and longer telomere lengths have been found to be associated with increased cancer risk (Chen et al, 2014), the possible explanation of the latter suggested to be lying in the germline mutations of the telomere maintenance genes causing telomerase up-regulation (Chen et al, 2014).…”
Section: Dna-related Factormentioning
confidence: 99%
“…Furthermore, the telomere length is heritable to a significant extent (Samavat et al, 2021;Vaiserman and Krasnienkov, 2021). Contrary to the above-mentioned studies in which TL was measured in peripheral blood, a more recent study in which TL was measured in cancer cells and cancer-associated fibroblasts (CAFs) found longer telomeres to be associated with worse prognosis in adenocarcinoma and squamous cell carcinoma and acknowledged it as a novel biomarker for the diagnosis of aggressive cancers with poor prognoses (Matsuda et al, 2023). In studies exploring the role of cancer cell telomere length in cancer risk, both shorter and longer telomere lengths have been found to be associated with increased cancer risk (Chen et al, 2014), the possible explanation of the latter suggested to be lying in the germline mutations of the telomere maintenance genes causing telomerase up-regulation (Chen et al, 2014).…”
Section: Dna-related Factormentioning
confidence: 99%
“…CAFs have also been identified in precancerous lesions of the blood, for example, monoclonal gammopathy of unknown significance [181][182][183] and the breast. Tenascin, which is a marker for CAFs [184], has also been detected in precancerous breast lesions as well as in ductal or lobular carcinoma in situ [185][186][187][188][189][190][191][192][193].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…In addition, telomere length was found significantly shortened in chronic myeloid leukemia [ 6 ]. However, in most solid tumors such as glioma [ 7 ], lung adenocarcinoma [ 8 ], neuroblastoma [ 9 ], bladder cancer [ 10 ], melanoma [ 11 , 12 ], hepatocellular carcinoma [ 13 ], and kidney cancer [ 14 ], the telomere length was increased compared with normal tissues [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%